The Influence of Brand Image and Service Quality on the Intention to Recommend Maxim Online Transportation Services in Mataram City with Brand Trust as a Mediating Variable - Dewi Fitriani; Lalu Adi Permadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of brand image and service quality on recommendation intention of Maxim online transportation service in Mataram City with brand trust as a mediator, amidst tight competition where Maxim has a Top Brand Index of only 2.8% in 2024. The main objective is to test the direct and indirect relationships between these variables. Using a causal associative quantitative approach with purposive sampling on 200 respondents Maxim users aged ≥17 years who are active on social media. The instrument in the form of a Likert scale questionnaire was analyzed using SmartPLS for validity, reliability, and hypothesis testing. The results show all significant paths: brand image (β = 0.588 to brand trust; β = 0.216 directly to recommendation intention), service quality (β = 0.649 to brand trust; β = 0.320 directly), and brand trust (β = 0.589 to recommendation intention), with full mediation and R² = 87.9%. The conclusion implies a strategy to improve brand image and service to increase consumer recommendations.